Inverted papilloma of the urinary bladder: A rare cause of haematuria in a young girl - Kamarulzaman, Mohd Nazli; Che Mohamed, Siti Kamariah; Abdul Aziz, Azian; Ghazali, Hamid (Ministry of Health and Universiti Brunei Darussalem, 2014)
Inverted papilloma of the urinary bladder is rare. In the paediatric group, this condition is even more rare. To date only five cases have been reported in the English literature. Due to its rarity, the morphology and biological behaviour are still uncertain. We report a case of inverted papilloma of the urinary bladder in a 12-year-old girl who presented with recurrent haematuria. The patient’s symptoms resolved after endoscopic resection with no recurrence on cystoscopy surveillance for last two years. The magnetic resonance imaging features of this lesion are described.